PERAN LEMBAGA KONSULTASI DAN BANTUAN HUKUM DALAM MEMBERIKAN PENDAMPINGAN HUKUM BAGI MASYARAKAT TIDAK MAMPU - Ahmad Dasan; Susiyanto Susiyanto; Sinung Mufti Hangabei; Mikho Ardinata (Fakultas Syari'ah Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: One of the reasons why the poor need legal protection is the equality of citizens before the law, there is no gap between the people and those who have money and positions, where both have the status of citizens in accordance with the legal system. In an atmosphere of a criminal justice system that has not yet reached the point of integration, there is a need to defend poor people or groups. The purpose of this study was to determine the role of legal advice and support institutions in providing legal support and community empowerment to the underprivileged. Using an empirical legal approach, this research focuses on the activities of the Legal Aid and Consultation Institute at the University of Muhammadiyah Bengkulu in fulfilling its role. The results of the study show that the Legal Consultation and Aid Institute is obliged to provide free legal aid through legal aid providers, but the information on the provision of free or free legal aid is not optimal, so there are still many accused or suspects with the law in Conflicted, not receiving legal advice/assistance from legal aid providers, thereby rendering the user powerless to deal with allegations/accusations/charges from the state. Keywords: Legal Aid Institutions, Free Legal Aid, Underprivileged Communities